Lateral Transmission of Yeast Symbionts Among Lucanid Beetle Taxa - Ueki, Gaku; Zhang, Sheng-Nan; Zhu, Xue-Jiao; Wen, Xiu-Jun; Tojo, Koji; Kubota, Kôhei (Frontiers in Microbiology, 2021)
The lateral transmission process of yeast symbionts among stag beetle genera Platycerus and Prismognathus around the border between Japan and South Korea was estimated based on molecular analyses and species distribution modellings. Phylogenetic analyses were based on yeast ITS and IGS sequences and beetle COI sequences using Prismognathus dauricus from the Tsushima Islands and Pr. angularis from Kyushu, Japan, as well as other sequence data from our previous studies. The range overlap based on the species distribution model (SDM) and differentiation in ecological space were analyzed. Based on the IGS sequences, Clade II yeast symbionts were shared by Platycerus hongwonpyoi and Pr. dauricus in South Korea and the Tsushima Islands, and Platycerus viridicuprus in Japan. Clade III yeasts were shared by Pr. dauricus from the Tsushima Islands and Pr. angularis in Japan. During the Last Interglacial period when the land bridge between Japan and the Korean Peninsula existed, range overlap was predicted to occur between Pl. viridicuprus and Pr. dauricus in Kyushu and between Pr. dauricus and Pr. angularis in Kyushu and the Tsushima Islands. The ecological space of Pl. hongwonpyoi was differentiated from those of Pl. viridicuprus and Pr. angularis. We demonstrated the paleogeographical lateral transmission process of Scheffersomyces yeast symbionts among lucanid genera and species: putative transmission of yeasts from Pr. dauricus to Pl. viridicuprus in Kyushu and from Pr. angularis to Pr. dauricus in Kyushu or the Tsushima Islands. We also found that the yeast symbionts are likely being replaced in Pr. dauricus on the Tsushima Islands. We present novel estimates of the lateral transmission process of microbial symbionts based on phylogenetic, SDM and environmental analyses among lucanid beetles.